Species survival versus eigenvalues - Luiz Antonio Ribeiro de Santana; Yuri Dimitrov Bozhkov; Wilson Castro Ferreira (Abstract and Applied Analysis)
Mathematical models describing the behavior of hypothetical species in spatially heterogeneous environments are discussed and analyzed using the fibering method devised and developed by S. I. Pohozaev.